Resilience to Historical Human Manipulations in the Genomic Variation of Italian Wild Boar Populations - Scandura, Massimo; Fabbri, Giulia; Caniglia, Romolo; Iacolina, Laura; Mattucci, Federica; Mengoni, Chiara; Pante, Giulio; Apollonio, Marco; Mucci, Nadia (Frontiers in Ecology and Evolution, 2022)
Human activities can globally modify natural ecosystems determining ecological, demographic and range perturbations for several animal species. These changes can jeopardize native gene pools in different ways, leading either to genetic homogenization or, conversely, to the split into genetically divergent demes. In the past decades, most European wild boar (Sus scrofa) populations were heavily managed by humans. Anthropic manipulations have strongly affected also Italian populations through heavy hunting, translocations and reintroductions that might have deeply modified their original gene pools. In this study, exploiting the availability of the well-mapped porcine genome, we applied genomic tools to explore genome-wide variability in Italian wild boar populations, investigate their genetic structure and detect signatures of possible introgression from domestic pigs and non-native wild boar. Genomic data from 134 wild boar sampled in six areas of peninsular Italy and in Sardinia were gathered using the Illumina Porcine SNP60 Beadchip (60k Single Nucleotide Polymorphisms – SNPs) and compared with reference genotypes from European specimens and from domestic pigs (both commercial and Italian local breeds), using multivariate and maximum-likelihood approaches. Pairwise FST values, multivariate analysis and assignment procedures indicated that Italian populations were highly differentiated from all the other analyzed European wild boar populations. Overall, a lower heterozygosity was found in the Italian population than in the other European regions. The most diverging populations in Castelporziano Presidential Estate and Maremma Regional Park can be the result of long-lasting isolation, reduced population size and genetic drift. Conversely, an unexpected similarity was found among Apennine populations, even at high distances. Signatures of introgression from both non-Italian wild boar and domestic breeds were very limited. To summarize, we successfully applied genome-wide procedures to explore, for the first time, the genomic diversity of Italian wild boar, demonstrating that they represent a strongly heterogeneous assemblage of demes with different demographic and manipulation histories. Nonetheless, our results suggest that a native component of genomic variation is predominant over exogenous ones in most populations.